MENTAL DISORDERS AND YOU An illustrated and easy handbook of mental disorders and mental health for the mentally ill, their families and the community - DR. ARUN RUKADIKAR; DR. MARY PONNAIYA RUKADIKAR (MIRAJ PSYCHIATRIC CENTRE DR. GAIKWAD ROAD, MIRAJ - 41640, 2007)
This book has come out of the authors' experience of more than four decades in helping the mentally ill, their families and the community to develop mental health literacy.